Learner perception and its implications on implementations of e-learning in an organisation - Teo, Siew Chin. (2008)
This project studies the learner perception in various aspects of e-learning, namely the content, collaboration, communications, evaluation, cognitive/emotive and performance support, technical support and community of practice. Results showed that they generally positive about e-learning and were ready for most aspects except online collaboration.